A Comparative Study of Numerical Methods for Predicting Crack Propagation in Reinforced Concrete Hollow Core Slabs (Journal of Civil Engineering Researchers, 2024)
Hollow core slabs are commonly used in prefabricated building construction and are calculated and constructed using gravity loads. The dead loads of the structure are reduced by using this slab system. Different criteria, such as the initiation and propagation of cracks in the hollow core slab, are used to analyze these slabs. Fracture mechanics is the basis for studying crack propagation. The present study was conducted to analyze the propagation of cracks in hollow core slabs under common loading conditions using the finite element method and numerical modeling to analyze cracks in reinforced concrete members. This research is theoretically conducted using finite element software. This research takes into account the potential varieties of cracks in concrete slabs. Slabs should consider all three types of cracks, which are shear, flexural, and flexural-shear cracks obtained from the reference test. Two Contour integral and XFEM methods are used to analyze cracks in Abaqus software. To validate and control the modeling process, the laboratory results of the research of Ibrahim N. Najma, Raid A. Daudb, and Adel A. Al-Azzawi. December 2, 2019, has been used. The outcomes of this study showed that the probability of the formation of a flexural-shear crack in the slab is higher than in other crack forms.
Keywords: CDP Numerical Method; Crack Growth; Reinforced Concrete Slab; Hollow core slab; XFEM method; reinforced concrete hollow slab; Contour integral method